Service provider - customer interactions: Key to success of innovative services - Antje Hoffmann; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2005)
The majority of service providers have recognized the need to develop innovative services that meet sophisticated customer needs on time. Because of structural changes in the market, rising costs and shorter lifecycles of services and technologies this has become a more demanding task than ever before. Most of the existing research focuses on the development of products rather than services. However, research in service related innovation activities is highly rewarding, as the service market is about to become a dominant factor of economic development. The objective of this paper is to provide an overview of the current state of interaction research with special focus on service marketing and service purchasing processes. A short presentation of the most important theoretical results and findings from empirical studies will be given. Furthermore, we will present results from our own case study investigating the IT Service industry. In this context, we have identified three different approaches of successful interactions between service providers and potential buyers during marketing and purchasing processes with innovative results. We will describe these approaches, show their similarities and differences and as a result, provide recommendations for the service industry and potential buyers.
urn:nbn:de:gbv:830-opus-1228
Keywords: 650; service provider; service market; service marketing; service purchasing